2023
DOI: 10.3389/fphys.2023.1130389
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference in cytochrome P450 monooxygenase (CYP) gene results in reduced insecticide resistance in Megalurothrips usitatus Bagnall

Abstract: Genes of the cytochrome P450 (CYP450) superfamily are known to be involved in the evolution of insecticide resistance. In this study, the transcriptomes of two Megalurothrips usitatus Bagnall (Thysanoptera: Thripidae) strains (resistant and susceptible) were screened for detoxification genes. MusiDN2722 encodes a protein composed of 504 amino acid residues with a relative molecular mass of 57.3 kDa. Multiple sequence alignment and phylogenetic analysis showed that MusiDN2722 is a member of the CYP450 family an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It was reported that CYP321B1 participated in insecticide detoxification of Spodoptera litura [ 34 ]. In Megalurothrips usitatus Bagnall, RNA interference of the CYP450 gene resulted in reducing pesticide resistance [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that CYP321B1 participated in insecticide detoxification of Spodoptera litura [ 34 ]. In Megalurothrips usitatus Bagnall, RNA interference of the CYP450 gene resulted in reducing pesticide resistance [ 35 ].…”
Section: Introductionmentioning
confidence: 99%